2020
DOI: 10.12913/22998624/127796
|View full text |Cite
|
Sign up to set email alerts
|

Low Temperature Combustion of Jet Propellant-8 Fuel in Compression Ignition Engine with the Low Compression Ratio

Abstract: Jet Propellant-8 (JP-8) is used as a fuel for a standard Compression Ignition (CI) engine instead of diesel oil, especially in the military applications. The properties of a kerosene-type fuel, which is JP-8, encourage us to test different strategies of mixture creation and combustion, which could be more effective for this fuel than these elaborated for diesel oil. The experiment aimed to show whether it is possible to realise an effective Low Temperature Combustion (LTC) strategy in a CI engine with a low co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…The experiment described in [33] confirmed that it is possible to realize an LTC process for the JP-8 fuel in a CI engine equipped with a common rail system with low CR (12:1), but the HCCI strategy could be applied only for the limited engine load. The results described in this paper show that the active space creation (the first step of HCCI combustion process) and the synchronization of a main dose injection timing with the start of the second stage of quasi-homogeneous mixture combustion (realization of PPC strategy with carefully chosen injection parameters) can be a method of effective fueling of CI engine with a low compression ratio with the use of different fuels.…”
Section: Resultsmentioning
confidence: 61%
See 1 more Smart Citation
“…The experiment described in [33] confirmed that it is possible to realize an LTC process for the JP-8 fuel in a CI engine equipped with a common rail system with low CR (12:1), but the HCCI strategy could be applied only for the limited engine load. The results described in this paper show that the active space creation (the first step of HCCI combustion process) and the synchronization of a main dose injection timing with the start of the second stage of quasi-homogeneous mixture combustion (realization of PPC strategy with carefully chosen injection parameters) can be a method of effective fueling of CI engine with a low compression ratio with the use of different fuels.…”
Section: Resultsmentioning
confidence: 61%
“…Lower octane fuels (such as diesel oil, n-heptane, DME and JP-8) burned in homogeneous charge compression ignition (HCCI) processes exhibit a two-stage ignition [24,33]. The first stage is low temperature heat release (LTHR) or "cool-flame" oxidation reactions (Fig.…”
Section: The Injection Strategy For CI Engine With a Low Compression Ratiomentioning
confidence: 99%
“…2 ). The phenomenon was also observed in the experiment carried out on the engine with a low compression ratio (CR = 12) fueled with homogeneous mixtures of JP-8 16 . For leaner mixtures, the combustion process was retarded, but the high rate of cylinder pressure rise (dp/dα) was not acceptable.…”
Section: The Idea Of the Efu And Its Experimental Verificationmentioning
confidence: 58%
“…The combustion process organisation in the CI engine determines the engine emissions and their efficiency. Despite the development of a homogeneous charge compression ignition (HCCI) process, which is very demanding in terms of combustion control 15 , 16 the CI engine's dominant strategy is Partial Premixed Combustion (PPC) 17 – 19 . Fuel is directly injected into the combustion chamber in PPC mode, and a stratified premixed charge is burned in a controlled way (Fig.…”
Section: Mixture Creation and Combustion Process In CI Enginementioning
confidence: 99%